Eco-evolutionary feedback in fish–zooplankton communities on the Scottish island of North Uist - Chitheer, T. (2018)
‘Eco-evolutionary feedbacks’ occur when evolution of organismal traits causes environmental change that drives further evolution. Predator and prey interactions provide good examples of eco-evolutionary feedbacks. Here I examine the potential for eco-evolutionary feedbacks between three-spined sticklebacks (Gasterosteus aculeatus, hereafter ‘stickleback’) and their zooplankton prey in lochs (lakes) on the Scottish island of North Uist. Many lochs on the island were colonised by sticklebacks after the last glaciation, approximately 10,000-15,000 years ago. Previous work has shown that sticklebacks in different lochs have diverged greatly from each other in response to local environments. On the other hand, apart from several very old studies on the occurrence of some zooplankton species, there have been no previous in depth studies on the population dynamics of zooplankton on North Uist. I investigated first the diversity and abundance of zooplankton groups and the most common species across all North Uist lochs. Thirty-nine species were classified from three main groups (Rotifera, Cladocera and Copepoda). Species abundance in the presence of fish was relatively more even, while the abundance of zooplankton groups was not generally related to fish presence except for Cladocera in a subset of locations. The effects of predation on the life-history of zooplankton were also examined by comparing reproductive traits of the dominant cladoceran species (Bosmina and Daphnia) in lochs with and without fish. Cladocerans in lochs with fish have more rapid reproductive cycles and higher fecundity parameters, probably in response to the increased threat of predation. These effects remain evident in Bosmina after they have been raised through three generations in the laboratory, supporting the hypothesis that they have a genetic basis and are not a plastic response to predator presence. Life-history variables of cladocerans were also related to abiotic and biotic variation among lochs, including depth, pH, chlorophyll levels and the concentration of alkaline metals. I also demonstrate that stickleback have diversified greatly among lochs in functional trophic traits that determine the efficiency of feeding on different types of prey, which could affect total primary production and the structure of prey communities. Ancestral stickleback populations have adapted according to the type of habitat colonised. Fish feed on benthic prey in shallow lochs, which requires greater effort for successful foraging than that required by fish that feed on planktonic prey. I found that variation in stickleback trophic traits was related to both abiotic and biotic variation among lochs, including loch depth and the mean contributions of planktonic and benthic prey to diet. The results presented in this thesis suggest the possibility of eco-evolutionary feedbacks in these simple ecosystems on North Uist based on the significant responses in fish and zooplankton communities. The thesis also provides a basis for further studies on fish-zooplankton interactions on North Uist and contributes to the wider body of knowledge concerning the relevance of natural variation in shaping the foraging mechanisms of animals.